Nerve growth factor and post-infarction cardiac remodeling - O. Yu. Kytikova; T. P. Novgorodtseva; М. V. Antonyuk; Yu. K. Denisenko; O. V. Atamas (Acta Biomedica Scientifica, 2022)
The prevalence of sudden death from chronic heart failure and cardiac arrhythmias caused by myocardial infarction is a complex problem in cardiology. Post-infarction cardiac remodeling occurs after myocardial infarction. This compensatory-adaptive reaction, regulated by mechanical, neurohumoral and genetic factors, includes the structural and functional changes of cardiomyocytes, stromal elements and extracellular matrix, geometry and architectonics of the left ventricular cavity. Adverse left ventricular remodeling is associated with heart failure and increased mortality. The concept of post-infarction cardiac remodeling is an urgent problem, since the mechanisms of development and progression of adverse post-infarction changes in the myocardium are completely unexplored. In recent years, the scientist attention has been focused on neurotrophic factors involved in the sympathetic nervous system and the vascular system remodeling after myocardial infarction. Nerve growth factor (NGF) is a protein from the neurotrophin family that is essential for the survival and development of sympathetic and sensory neurons, which also plays an important role in vasculogenesis. Acute myocardial infarction and heart failure are characterized by changes in the expression and activity of neurotrophic factors and their receptors, affecting the innervation of the heart muscle, as well as having a direct effect on cardiomyocytes, endothelial and smooth muscle vascular cells. The identification of the molecular mechanisms involved in the interactions between cardiomyocytes and neurons, as well as the study of the effects of NGF in the cardiovascular system, will improve understanding of the cardiac remodeling mechanism. This review summarizes the available scientific information (2019–2021) about mechanisms of the link between post-infarction cardiac remodeling and NGF functions.